Pengaruh Lingkungan Kerja Non-Fisik terhadap Organizational Citizenship Behavior Guru dengan Perceived Organizational Support sebagai Variabel Mediator - Yono Yono; Rahmi Lubis; Yudistira Yudistira (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This research seeks to evaluate how the non‑physical work setting influences teachers’ Organizational Citizenship Behavior (OCB), to evaluate its effect on Perceived Organizational Support, and to examine the relationship between Perceived Organizational Support and OCB, and to assess whether Perceived Organizational Support acts as a mediator linking the non‑physical work environment to OCB. An explanatory quantitative design was employed. The target population comprised all teachers at the study site, A total of 279 teachers were selected using proportional random sampling. Information was collected through Likert‑scale questionnaires, The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS‑SEM). The findings reveal that the non‑physical work environment positively and significantly impacts OCB (path coefficient = 0.803, t = 20.404, p = 0.000). It also emerges as a strong predictor of Perceived Organizational Support (coefficient = 0.938, t = 138.834, p = 0.000). Moreover, perceived Organizational Support positively and significantly affects OCB (coefficient = 0.183, t = 4.508, p = 0.000) and functions as a crucial mediator in the relationship (mediation coefficient = 0.172, t = 4.493, p = 0.000). These results suggest that a supportive work environment enhances employees’ perception of organizational support, which in turn boosts teachers’ propensity to engage in extra‑role activities that benefit the school.